Transformando normas e Padrões: as práticas informacionais de pessoas trans na “reinvenção do corpo” - Flávia Virgínia Melo Pinto (2020)
This is a qualitative study that explores the information practices of transsexual people in their gender transition processes. The concerns that motivated us were: what were the informations requested from transsexual men and women when they realized the conflicts with the gender designated at birth? How did transsexual people appropriate information to create conceptions of themselves? How does information sharing between transsexual people happen to reinvent the body? The general objective was to identify the demands for information from transsexual people in the construction of their identities, from their life reports, identifying the contradictions and barriers faced by them in these processes. For data collection, we conducted in-depth interviews with nine collaborators, based on a semi-structured script. An analysis of the data was made from the theoretical-methodological conceptions of dialectical hermeneutics to interpret the reports and remove the themes and categories that were discussed with an interlocution between the concepts of the social approach of Information Science, the gender theories and the Pierre Bourdieu's praxiological theory. Considering the generified conceptions that conform the inhabit of the individuals of our society, producing male-bodies and female-bodies to maintain heteronormativity (BENTO, 2006), the individuals position themselves in the gender field with their respective cultural and symbolic capitals, in a dispute around gender norms. As transsexual people occupy a position of heterodoxy, demanding information to solve their conflicts with the gender indicated at birth and in search of the gender passability that guarantee their social acceptance. At the same time, they produce new knowledge in your daily practices, when experiencing their desires, constructing new conceptions of themselves. This knowledge is used in everyday life and in the political organization of this segment for civil rights. The people experience contradictions, they face barriers in the search for information, which are consequences of normative system that marginalizes the experiences that escape the historically constituted rules and established as eternal and immutable. In this process, the internet expanded the possibilities for interaction between these people, allowing them to be anonymous or the opportunity to show themselves and relate their transition experiences, constituting sources of information about the complex phenomenon of transsexuality.